Implementasi Metode Analytical Hierarchy Process Pada Sistem Pendukung Keputusan Rekomendasi Ikan Budidaya Berbasis Web - Anggi Masdalena; Ruri Ashari Dalimunthe; Endr Saputra (Building of Informatics, Technology and Science (BITS), 2022)
Aquaculture in Asahan Regency still has high potential. The large number of residents who have vacant locations/land, becomes a good potential to be managed. The problem that is often faced is that residents have difficulty in determining the type of fresh or brackish water fish to be cultivated. The Asahan District Government through the Asahan District Fisheries Service has launched a program to increase the production of fresh and brackish water fish. To support this program, residents are expected to be able to take advantage of the potential of existing ponds. Therefore we need a system that can be used to assist the government in determining the types of fish farming that have potential. The purpose of this freshwater fish farming decision support system can provide information about the types of freshwater fish seeds, as well as assist farmers in making decisions about freshwater fish seeds. The research approach uses quantitative methods with program design using the Analytical Hierarchy Process (AHP) method. The results of calculations using pairwise comparison matrices for the use of criteria indicate that the most important priority is shown in the water temperature of 0.39, the second priority is water brightness of 0.41, the third priority is the pH of the water at 0.10, the fourth priority is the type of pond at 0.066, and the fifth priority is The pond area is 0.041. Meanwhile, for alternative uses, data is obtained, namely the weight of the highest value of Fishery Cultivation Potential, namely Rawang Panca Arga with a value of 0.6224, the second alternative is Bandar Pulau with a value of 0.6215 and the third alternative is Bandar Pasir Mandoge with a value of 0.575